A versatile, low-cost drying kiln for opening pine cones - Robbins, A (Commenwealth Forestry Institute, University of Oxford, 1985)
A batch type, forced draught kiln is described, used principally for drying cones of Pinus caribaea and P. oocarpa in the Republic of Honduras, C.A.. Ventilation is by means of two, large diameter fans powered by an electric motor, gasoline or diesel engine. Air may be passed once through the kiln, or recirculated. Heating is by means of a furnace and flue radiator, using waste cones or firewood as fuel. Temperature is controlled manually with a precision of +/- landdeg;C. Cones or other products to be dried are placed in stacked trays, which can also be used for sundrying or precuring. Total capacity of the kiln is 3200 litres of closed cones. The design is simple, and all parts (including fans and heating system) can be made from material normally available locally in developing countries. The design should be suitable for countries that are initiating pine seed collection programmes. It is suitable for other forestry species, and should have application for drying agricultural products as well. Detailed plans are included, with notes on operation and construction.